The classical idea - Dunlop, Geoff; Silleck, Bayley (Art of the Western world / executive producer, Perry Miller Adato, 1989)
Traces the origins of humanism and immortal classical style to Ancient Greece. Probes Greek art and architecture and studies the Parthenon. Shows how thw genius of Roman engineering and architecture was used to build an empire, while portrait sculptures exalted its rulers.